Integrating Deep Learning into English Teaching: Developing Students' Skills at Senior High School - Shinta Ayu Pramudya; M Rikza Chamami; Awwalia Fitrotin Izza (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This case study was conducted to discuss the limitations of the pedagogical implementation of deep learning (DL) in English language teaching (ELT) in Indonesian high schools. The purpose of this study was to theoretically explore how the pedagogical application of deep learning is conceptualized in English language classrooms and how it contributes to the development of students' learning skills, with Senior High Schoolas the research object. Using a qualitative case study design, senior high school teachers (T=3) and students (S=42) were the study subjects. The main data were collected through semi-structured interviews with English teachers and supported by structured interviews given to 11th-grade students whose learning process had been implemented by deep learning. The findings indicated that deep learning contributes positively to the development of students' skills. Deep learning is an educational process that creates meaningful learning through real-world experiences. Teachers use interactive techniques, such as problem-solving and project-based learning, which are interspersed with traditional methods, including jigsaw. The results show that each individual experienced some improvement in their language skills, such as speaking, reading, and several other skills, through learning by applying teamwork, project-based learning, problem analysis, and creative expression skills. Additionally, several challenges related to its integration were identified. These have been identified to maximize the application of deep learning in English language teaching (ELT) and improve student learning skills (SLS) in Indonesia. This study concludes that institutional support, professional development for teachers, and improved digital literacy are still greatly needed and must be implemented consistently.